A conserved BAH module within mammalian BAHD1 connects H3K27me3 to Polycomb gene silencing. Issue 8 (6th April 2021) - Fan, Huitao; Guo, Yiran; Tsai, Yi-Hsuan; Storey, Aaron J; Kim, Arum; Gong, Weida; Edmondson, Ricky D; Mackintosh, Samuel G; Li, Haitao; Byrum, Stephanie D; Tackett, Alan J; Cai, Ling; et al.
Abstract: Trimethylation of histone H3 lysine 27 (H3K27me3) is important for gene silencing and imprinting, (epi)genome organization and organismal development. In a prevalent model, the functional readout of H3K27me3 in mammalian cells is achieved through the H3K27me3-recognizing chromodomain harbored within the chromobox (CBX) component of canonical Polycomb repressive complex 1 (cPRC1), which induces chromatin compaction and gene repression. Here, we report that binding of H3K27me3 by a Bromo Adjacent Homology (BAH) domain harbored within BAH domain-containing protein 1 (BAHD1) is required for overall BAHD1 targeting to chromatin and for optimal repression of the H3K27me3-demarcated genes in mammalian cells. Disruption of direct interaction between BAHD1 BAH and H3K27me3 by point mutagenesis leads to chromatin remodeling, notably, increased histone acetylation, at its Polycomb gene targets. Mice carrying an H3K27me3-interaction-defective mutation of Bahd1 BAH causes marked embryonic lethality, showing a requirement of this pathway for normal development. Altogether, this work demonstrates an H3K27me3-initiated signaling cascade that operates through a conserved BAH 'reader' module within BAHD1 in mammals. Graphical Abstract: